Enhancement of Mechanical and Structural Traits of Aluminum Using Low Energy Plasma Focus Device. Issue 18 (14th May 2019) - Raza, Hafiz Ahmad; Shafiq, Muhammad; Naeem, Muhammad; Naz, Muhammad Yasin
Abstract: Owing to good machinability, low weight and high specific strength, aluminum is widely used in aerospace and automotive industries. However, low mechanical strength limits its wide spread use in mainstream industries. In this study, nitriding of aluminum was performed with a stream of low energy ions in 1.8 kJ Mather type dense plasma focus (DPF) device. The axial distance from the anode tip was varied in steps to study the effect of the stream length on structural and mechanical properties of the nitrided samples. XRD and Raman analysis confirmed the formation of aluminum nitride (AlN) on the plasma exposed surface. Williamson‐Hall (W−H) study revealed significant improvement in crystallinity and strain of the nitride samples. The most favorable results on mechanical and structural properties of the nitrided samples were obtained at an axial distance of 10 cm. The improved texture and maximum dislocation density for typical AlN (311) is obtained at the optimum distance. The micro‐hardness of the nitrided samples was measured ∼4.5 times higher than the base material. Abstract : Nitriding of aluminum is successfully achieved using dense plasma focus device without any additional processing for the removal of the oxide layer. The XRD of processed samples shows the presence of aluminum nitride phase, which is further verified by using Raman spectroscopy. The effect of axial position on surface properties shows the highest hardness, maximum strain and dislocation density is obtained at 10 cm distance.